Public Policy and Manpower Development - Sexton, Jean (Relations industrielles / Industrial Relations, 1975)
This article reviews "Public Policy and Manpower Development" by John W. Holland and Michael L. Skolnik.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z